Iustus Lipsius Europae Lumen et Columen - De Landtsheer, Jeanine (Supplementa Humanistica Lovaniensia, 1999)
Some six years ago the 500th anniversary of the birth of the Spanish-Dutch humanist Juan Luis Vives celebrated in Spain and especially in his hometown Valencia. On a much smaller scale Leuven also contributed to the celebration of this humanist, who outdid even the great Erasmus in originality of ideas in the field of pedagogy, psychology and sociology. At that time already it was obvious to me that the most important humanist of our own region, Justis Lipsius from Overijse, deserved to be honoured in a more conspicuous way than previously. In happy collaboration with Lipsius's hometown of Overijse and with the Plantin-Moretus Museum at Antwerp, a most varied and attractive programme was designed, including several exhibitions, a historical evocation of the man and his world, and a few publications.